1991
DOI: 10.3109/00016489109100758
|View full text |Cite
|
Sign up to set email alerts
|

The HLA System and T-Cell Subsets in Bell's Palsy

Abstract: The etiology of Bell's palsy (BP) is still unknown, but infectious, immunological and genetic factors have been suggested to play a role in the pathogenesis of the disease. We analyzed blood samples of 92 Mexican Mestizo patients diagnosed as having BP according to established international criteria, and the results were compared to a group of apparently healthy controls of the same ethnic origin. HLA class I (A, B, C) and Class II (DR, DQ) products of the major histocompatibility complex (MHC), and the percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Class I (A, B, C) HLAs were investigated by testing for microlymphocyte toxicity [4] in the medical biology department of the medical Faculty of Istanbul University [4].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Class I (A, B, C) HLAs were investigated by testing for microlymphocyte toxicity [4] in the medical biology department of the medical Faculty of Istanbul University [4].…”
Section: Methodsmentioning
confidence: 99%
“…A family history is present in 4-14% of these cases [1,7,12]. The etiology of IFP is still unknown, but infec-tious, immunologic and genetic factors have been suggested to play a role in the pathogenesis [3,4,6]. A number of reports on familial IFP have suggested that hereditary components might play a role in the etiology of the disease [9,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4The bony fallopian canal is normal, with no sign of facial nerve compression by the fallopian canal bone [60][61][62][63] In recent years, it is found that the mean neutrophil-to-lymphocyte ratio and neutrophil values were higher in adult and pediatric patients with Bell's palsy [64,65] Similar changes in peripheral blood leukocyte subpopulations are also described in the process of a few inflammatory demyelinating diseases, such as during the acute stage of Guillain-Barré syndrome and in acute exacerbations of multiple sclerosis. Bell's palsy, such as Guillain-Barré syndrome, may be an acute demyelinating disease of the peripheral nerve system [68] An examination of the serum samples from patients with Bell's palsy showed elevated concentrations of cytokines interleukin-6 (IL-6), interleukin-1 (IL-1), and tumor necrosis factor-alpha (TNF-α) were increased compared with control groups [69,70] In contrast to control populations, decreased percentages of total T cells (CD3) and T helper/inducing cells (CD4) have also been found in the acute phase of the disease. An obviously decreased peripheral blood T lymphocyte percentages and an increase in B lymphocyte percentage in BP have been found within the first 24 days from the clinical onset of the paralysis.…”
Section: Anatomical Structurementioning
confidence: 99%
“…Several possible causes have been proposed for familial Bell's palsy and they include: 1) inherited anatomical abnormality; [6] 2) vascular risk factors (e.g., diabetes or glucose intolerance and hypertension); [4,7] and 3) immunogenetic factors. [8] Of these factors, inherited anatomical abnormality of the facial cannal is the most commonly proposed cause for familial Bell's palsy. [6,9] In patients with no good recovery within three months, further investigations, especially radiological investigations may be warranted to exclude facial cannal abnormalities.…”
Section: Discussionmentioning
confidence: 99%